Intervenciones de enfermería y su influencia en las medidas de bioseguridad de los pacientes hospitalizados. Hospital General IESS Babahoyo. Junio – octubre 2023 - Moncada Macias, Adrián Javier (2023)
Nursing intervention is defined as any treatment, based on clinical judgment and knowledge, performed by a nursing professional to improve patient outcomes. (EnfermeriaActual, 2022). It is very important since these are the ones that complement the help or supply the care that people and the environment need. The WHO describes biosafety as a set of standards and procedures to protect the health of personnel against various risks, whether biological, chemical, or physical, to which they may be exposed during the care provided to the user. The different activities carried out by health personnel carry some risk factors, which require biosafety measures to be applied. Biosafety constitutes a vital component of the quality assurance system, and must be understood as a doctrine aimed at achieving attitudes and behaviors that reduce risk. The attitude towards safe practices of each of the team members determines their own safety, as well as that of their colleagues and the community in the work area. It is the obligation of health personnel to follow the guidelines of the biosafety standards of their establishment, in order to guarantee safe work, and also of the health establishment to provide the necessary implements to guarantee this principle.